INFLUENCE OF MANUAL THERAPEUTICAL MANEUVERS APPLICATION ON THE AUTONOMIC NERVOUS SYSTEM OF HIPERTENSIVE SUBJECTS THROUGH THE HEART RATE VARIABILITY ANALYSIS: PILOT STUDY (Fiep Bulletin - online, 2014)
The Arterial Pressure is detected by mechanoreceptors situated in the Aorta and Carotids walls. In the hypertension the regulating mechanisms of the arterial pressure are less sensible, diminishing the reflexes, having a lesser number of action potentials of the nerve depressors. The Heart Rate Variability reflects the state and the function of the central oscillators and peripheral reply to the central autonomic work for the sympathetic or parasympathetic activity. This study had as objective to analyze the influence of manual therapeutic maneuvers application on the autonomic nervous system and the arterial pressure of hypertensive subjects. The sample constituted of 6 subjects, with average age of 60 years, classified as pre-hypertensive and hypertensive, as the Brazilian Society of Cardiology, submitted to a heart rate variability analysis, arterial pressure monitoring and the application of four therapeutic maneuvers in the autonomic nervous system way. After the maneuvers application, it was observed a reduction in the pressure average of the individuals, however with statistical significance only in the diastolic. There was a sympathetic predominance, a hypertensive subjects characteristic, as much as after and before the maneuvers, being observed that this predominance reduced at the moment of the application, however increased in reply to the orthostatic test carried through after application. It can be affirmed that these maneuvers are capable to influence in the reduction of the diastolic arterial pressure.
Keywords: arterial pressure; heart rate variability; manual therapy